Model of Analysis of Energy Security and Work of Production Plants for Satisfaction of Own Needs - Shahbazyan, Khachik; Minasyan, Sergey (Bulletin of Yerevan University G: Economics, 2022)
In the energy sector, producers using renewable energy sources (RES) and other producers with a small capacity, in particular, plants with a capacity of up to 30 MW are of great importance. Taking into consideration the international experience in organizing the work of RES stations, it can be noted that it is expedient to build these stations to meet the needs of industrial enterprises, which makes it possible to increase significantly the efficiency of the energy system and the level of energy security. Given the difficulties associated with assessing and improving the level of energy security, it becomes necessary to develop a methodology for assessing and analyzing the level of energy security.In the process of developing the Methodology for assessing the energy security of the Republic of Armenia, it is necessary to highlight the assessment of the operating state of the system and the development of an optimal working model of generating plants as key components, at the same time, it is necessary to take into account the relationship between system reliability indicators and safety characteristics. At the same time, in a number of European countries, an important component of ensuring system security is the model of operation of autonomous generating stations (AGS) operating in the system.The paper analyzes the dependence of indicators characterizing the reliability of the RA power system in the RStudio programming system.
Keywords: energy security; reliability; management; electricity; regulation; generating station; relative weight